How ISIS addresses women from Western and Middle-Eastern backgrounds: A discourse analysis - Nassar, Kesmat Taha (AUC Knowledge Fountain, 2019)
Although the atrocities the Islamic State in Iraq and Syria (ISIS) commits against women on daily basis are no secret, hundreds of women from different parts of the world have pledged their allegiance to the terrorist group and many more are susceptible to radicalization. The group has capitalized on the opportunity the internet provides to spread their propaganda; however, this also means that it has provided researchers with a lot of accessible data to study. The focus of this thesis is on the language used in by ISIS in articles addressing women in its official online magazines. In order to look into how ISIS adapts its language to attract female recruits from different backgrounds, the research was conducted on a number of English articles selected from Dabiq and Rumiyah magazines and a number of Arabic articles from Al-Naba' newsletter. These articles were examined for lexical choices, pronominal use, metaphors, and absolutist reasoning. Then, on the macro level, the discursive approaches employed in these articles was compared and contrasted with each other to provide a clearer image of the roles portrayed for the female recruits and the power relations emphasized in the discourse. The analysis showed a focus in the English data on the roles of women as a member of a family and community who is often addressed in a familiar tone and given the illusion of having the space to negotiate her role. On the other hand, the Arabic data introduced the role of the physical fighter to its audience in texts heavily saturated with absolutist reasoning. This marks the beginning of a new and worrying trend for terrorist groups that have had little use for tailored content and culture sensitivity before.